171 Alemtuzumab induced neutropaenia: women at risk. Issue 12 (14th November 2019) - Tanveer, Riffat; Pace, Adrian; Rog, David; Nazar, Sharaf; Talbot, Paul; Jackson, Fran; Mihalova, Tatiana
Abstract : Background: Alemtuzumab, a CD52 - specific monoclonal antibody depletes T and B cell population to reduce relapse in multiple sclerosis. Neutrophils also express low levels of CD52 and can be depleted transiently by alemtuzumab, increasing the risk of infection in the post-alemtuzumab treatment period. Aim: In this study in the Greater Manchester Neuroscience Centre (GMNC) we investigated at risk population for alemtuzumab induced neutropaenia. The outcome of these patients is also discussed. Method: Retrospective study of patients who developed neutropaenia following treatment with alemtuzumab at the GMNC. Data of patient demographics, grade of neutropeania, symptoms while neutropaenic and management were evaluated. Results: Of the 131 patient (86 F: 45 M) treated with alemtuzumab (1.9 F: 1 M ratio), 18 patient (13.7%) developed neutropaenia (17 F Vs 1 M, 19.8% F Vs 2.2% M). Moderate to severe (grade 2–4) neutropaenia was only observed in females. Average duration to develop neutropaenia was 41 days. While neutropaenic 16 patients were asymptomatic, 1 developed flu-like illness and 1 had recurrent chest infection requiring antibiotic. Conclusion: In our experience, women are at significantly higher risk of alemtuzumab induced neutropaenia. Monthly serial blood monitoring is adequate for most patients and specific intervention rarely required.